PENGARUH EKUITAS MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PAKAIAN ANAK OSELLA KIDS MATAHARI DEPARTMENT STORE MANHATTAN MEDAN) - Clara Merya; Hernawaty Hernawaty; Cahyo Pramono (Ensiklopedia Education Review, 2021)
This study aims to explain the effect of brand equity (X1), price (X2) and promotion (X3) on purchasing decisions (Y) in a case study of Osella Kids Matahari Children's Clothing, Manhattan Department Store, Medan. The population in this study were visitors to children's clothing Osella Kids Matahari Department Store Manhattan Medan using purposive sampling technique obtained a sample of 110 respondents and used a questionnaire to be used as a data collection method in this study. The analysis method in this study was using multiple linear regression analysis. The results of the analysis show that there is a partially significant effect between brand equity and price on purchasing decisions, while partially promotion has no effect on purchasing decisions. And to simultaneously get that brand equity, price and promotion have a significant effect on purchasing decisions for children's clothing Ossela Kids Matahari Department Store Manhattan Medan.Keywords: Brand Equity, Price, Promotion, Purchase Decision.